2011
DOI: 10.5098/fhp.v2.2.3002
|View full text |Cite
|
Sign up to set email alerts
|

Bendable Heat Pipes Using Sintered Metal Felt Wicks

Abstract: This work describes the effect bending within the adiabatic section has on the performance of heat pipes. The heat pipes described herein are bendable post fabrication and are distinct from heat pipes fabricated in bent configurations and from flexible heat pipes. The effect of bending on performance and performance limits was both calculated and measured. The heat pipes used for testing were the copper-water variety. The wick was made from sintered copper felt and provided the bendability feature of these hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…10. Influence of bending on the trend of maximum capillary limit: case (A) [9], case (B) [16], case (C) [7], case (D) [17] and case (E) [18].…”
Section: Effect Of Inclination Angle On the Capillary Limit Of Bent H...mentioning
confidence: 99%
“…10. Influence of bending on the trend of maximum capillary limit: case (A) [9], case (B) [16], case (C) [7], case (D) [17] and case (E) [18].…”
Section: Effect Of Inclination Angle On the Capillary Limit Of Bent H...mentioning
confidence: 99%
“…The device transferred up to 12 W of power with an effective thermal conductivity of up to 830 W(m K) −1 . Odhekar et al [21] presented the results of testing a copper/water heat pipe with sintered copper fiber wicking from 0 • to 90 • flex. They found that the flex angle had little effect on the temperature distribution and resulting copper equivalence due to the deformability of the wick structure.…”
Section: Introductionmentioning
confidence: 99%